Fimepinostat, a novel dual inhibitor of HDAC and PI3K, effectively reverses HIV-1 latency ex vivo without T cell activation - Jesper D. Gunst; Kathrine Kjær; Rikke Olesen; Thomas A. Rasmussen; Lars Østergaard; Paul W. Denton; Ole S. Søgaard; Martin Tolstrup (Elsevier, 2019)
Objectives: To test the potential of fimepinostat (CUDC-907), a dual inhibitor of histone deacetylases (HDAC) and phosphatidylinositol-3-kinases (PI3K), to reverse human immunodeficiency virus type 1 (HIV-1) latency in infected cell lines and in CD4+ T cells from HIV-1-infected donors on long-term combination antiretroviral therapy (cART). Methods: Latently HIV-1-infected J-lat Tat-GFP and ACH-2 cell lines were stimulated with clinically relevant concentrations of fimepinostat using the HDAC inhibitors (HDACi) panobinostat and romidepsin for comparison. Next, CD4+ T cells from donors living with HIV-1 on long-term cART were stimulated ex vivo and cell-associated unspliced HIV-1 RNA was measured to quantify changes in HIV-1 transcription. Finally, the impact of fimepinostat on T cell activation (CD69 expression) and proliferation (Ki67 expression) was determined using peripheral blood mononuclear cells from uninfected donors. Results: We found fimepinostat to be a potent latency-reversing agent. This was true in two latently infected cell lines as well as ex vivo in CD4+ T cells isolated from donors living with HIV-1. Relative to therapeutic dosing levels, fimepinostat showed latency-reversing potential comparable to romidepsin, which is the most potent HDACi tested in HIV-1 cure-related trials. Interestingly, in contrast to romidepsin, fimepinostat stimulation resulted in decreased T cell activation and had no negative impact on T cell proliferation. Conclusions: At therapeutic concentration, the dual HDAC and PI3K inhibitor fimepinostat was a potent HIV-1 latency-reversing agent and it did not induce T cell activation and proliferation. The potential of fimepinostat as a latency-reversing agent warrants further investigation.